40TH ANNIVERSARY OF INSTITUTE OF INTERNATIONAL STUDIES: FROM A PROBLEM LABORATORY TO THE INSTITUTE OF INTERNATIONAL STUDIES - A. L. Chechevishnikov (Vestnik MGIMO-Universiteta)
Applied foreign policy analysis is the hallmark of MGIMO-University. 2016 marks 40th anniversary of introduction of this element to the identity of our university in a form of Problem Research Laboratory. MGIMO development as a leading think tank took place in cooperation with the Ministry of Foreign Affairs and in close cooperation with other key institutions that shape foreign policy and are responsible for ensuring the national interests of Russia in the world. Today MGIMO's priority is the development of political policy expertise and analytical development-oriented scientific and practical support of the activities of state bodies. Such studies are the main but not the only focus of the Institute of International Studies.